FOREIGN LOANS AND THE CHALLENGES OF NATION-BUILDING IN NIGERIA: HARVESTING INTERNAL POTENTIALS - OKAFOR, Uzodinma Chukwuemeka; ONONIHU, Simon C (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Over the years, most developing economies have sought loans from wealthy nations to aid them cushion the effects of protracted socio-economic debacles limiting their states. Nevertheless, the exercise instead of providing succour to these states turns out to chain not only their economies but the pace of political development. It is on that note that this study examined the non-productivity and performance of the loans borrowed as they remained major issue in question. It questioned the character of leadership in Africa, especially Nigeria with poor utilization capacity where loan is involved. As a matter of fact, the study adopted structural functionalism theory to examine the governmental ineptitude in harvesting internal potentials due to poverty of ideas. To articulate the argument of the study, it employed causal design utilising documentary method of data collection and was analysed qualitatively using descriptive method of data analysis. In conclusion, the study attests that the problem of Africa is bad leadership consequent upon extreme mismanagement of resources, poor vision, mission and goal oriented target. It explains the extent of government’s dependence on foreign loans without considering her untapped internal human and material resources. The paper recommends that government should explore local contents in addressing the problems of the state. This requires inward exploration of human and capital contents in the quest for the development of Nigeria.